2016
DOI: 10.1017/dmp.2016.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hurricane Sandy on Health Care Services Utilization Under Medicaid

Abstract: Results are consistent with previous investigations demonstrating that some of the greatest effects of a disaster on health services utilization occur well beyond the initial event. One-year effects, combined with some 3-month effects, suggests that storm recovery, with its effect on health care services utilization, may have followed different paths in areas designated as inside or outside the storm zone. (Disaster Med Public Health Preparedness. 2016;10:472-484).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Primary surge is defined as the need for health care during and immediately after an incident generated by trauma, injury, and illness caused by the incident, or by pre-existing chronic conditions not properly treated during the incident. 12,13 Followers of the news during Hurricane Sandy may recall that many health authorities also feared the emergence of other threats such as water-borne illnesses enabled by large bodies of standing water and disrupted public infrastructure. After all, the storm's passage over Haiti produced more than 9000 cholera cases, as reported by the Center for Economic and Policy Research.…”
mentioning
confidence: 99%
“…Primary surge is defined as the need for health care during and immediately after an incident generated by trauma, injury, and illness caused by the incident, or by pre-existing chronic conditions not properly treated during the incident. 12,13 Followers of the news during Hurricane Sandy may recall that many health authorities also feared the emergence of other threats such as water-borne illnesses enabled by large bodies of standing water and disrupted public infrastructure. After all, the storm's passage over Haiti produced more than 9000 cholera cases, as reported by the Center for Economic and Policy Research.…”
mentioning
confidence: 99%
“…The short-term challenges related to patient evacuation and absorbing citywide patient surge only highlight the most immediate social impacts of physical damage to hospitals, and secondary hospital "surge" issues need to be addressed. Studies have demonstrated that some of the greatest effects of a disaster on healthcare services utilization occur in the months and years following the immediate impact (Bell et al, 2018;McQuade et al, 2018;Sharp et al, 2016). According to one analysis, "disasters create a secondary surge in casualties because of the sudden increased need for long-term health care" (Runkle et al, 2012).…”
Section: Social Impactsmentioning
confidence: 99%
“…Although the mechanism through which disasters may affect long-term demand for healthcare services is not completely understood, it is well established that exposure to disasters poses particular challenges to individuals suffering from chronic health conditions such as heart disease, cancer, chronic respiratory, and diabetes (Mensah et al, 2005;Sharp et al, 2016). Therefore, hospital closures will likely have substantial and long-term consequences for the populations they serve.…”
Section: Social Impactsmentioning
confidence: 99%
“…Prior studies that examined the effects of hurricanes on health observed that increases in mortality and emergency department visits can persist for at least 1 year, especially for cardiovascular-related diseases. 1,2 Public health emergency response traditionally focuses on reducing mortality and preventing injuries during or immediately following a disaster; however, the longterm health effects remain unclear. Additionally, limited knowledge exists on the relationship between hurricanes and health outcomes for multiple morbidities.…”
mentioning
confidence: 99%
“…Previous publications that evaluated the effects of hurricanes on health assessed health outcomes among either the general population or the nonelderly Medicaid population; thus the elderly population has been overlooked. 1,2 The limited studies that evaluated the health of elderly dual-eligible Medicare-Medicaid beneficiaries found that they were generally frailer and had more chronic conditions than did individuals covered under other insurance types. 3,4 However, vulnerability to disasters such as hurricanes by race and gender among this group remains unknown.…”
mentioning
confidence: 99%